2020
DOI: 10.1371/journal.pone.0227014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and sex on taste function of healthy subjects

Abstract: The purpose of this study was to determine the influence of age and sex on the taste functions of healthy Taiwanese. Subjects were divided into groups based on their sex and age: 20-39 years, 40-59 years, or � 60 years. We evaluated the taste functions of subjects using the whole mouth suprathreshold taste test and the taste quad test. For the wholemouth test, subjects were instructed to sip and swish sweet, sour, salty, and bitter solutions, each at 5 different suprathreshold concentrations. Each subject was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 22 publications
0
27
0
1
Order By: Relevance
“…In line with previous reports, it was observed that men and women differ in their taste sensitivities, with women being more sensitive to sweet and salty than men. Some studies, comparing taste function between sexes, also reported higher taste sensitivity in females, comparatively to males (e.g., [27][28][29]), although some others only found differences between some age groups [30]. Different methodologies for assessing taste function and evaluations in populations with different genotypes, food habits, and health conditions may explain these diverse results among studies.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous reports, it was observed that men and women differ in their taste sensitivities, with women being more sensitive to sweet and salty than men. Some studies, comparing taste function between sexes, also reported higher taste sensitivity in females, comparatively to males (e.g., [27][28][29]), although some others only found differences between some age groups [30]. Different methodologies for assessing taste function and evaluations in populations with different genotypes, food habits, and health conditions may explain these diverse results among studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports on the associations between sex, taste, and fungiform papillae density have shown conflicting findings. Some studies have reported no sex related differences in fungiform papillae density [ 29 ] or taste [ 44 ], while others did find such differences [ 4 , 6 , 28 ]. Women have been shown to have higher taste sensitivity, and supertasters may be more common among women [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taste dysfunction has rarely been investigated in Asian populations [ 19 ]. Significant differences have been observed in taste recognition thresholds between different ethnic groups in the same region [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this study was conducted only in individuals aged younger than 65 years. Recent studies reported that age and sex are associated with taste alterations in 240 healthy Taiwanese individuals [ 19 ]. However, in this study, none of the individuals’ eating habits and nutritional intake were considered, and only four basic tastes (sweet, salty, bitter, and sour) were measured.…”
Section: Introductionmentioning
confidence: 99%